Role of imiquimod as adjuvant for vaccination against Leishmania major infection in BALB/c mice - Faramarz Dobakhti; Ghader Khalili; Hamid Mahmoudzadeh Niknam; Vahid Khaze; Fatemeh Partovi; Taraneh Naghibi Mahmoodabadi; Shahriar Aalinejad (Pasteur Institute of Iran, 2013)
Various adjuvants in combination with different antigens have been utilized as a vaccine candidate against leishmaniasis. However, the search for ideal adjuvants is still pursued due to the inefficiencies of current compounds. In the present study, the effect of imiquimod, as an adjuvant, is studied with soluble Leishmania antigens (SLA) in BALB/c mice. Four groups of mice were immunized with SLA, SLA plus imiquimod, SLA plus BCG, and PBS as control. Immunized mice received a boosting dose of SLA after 15 days. All groups were challenged with Leishmania major (L. major) promastigotes 2 weeks after the booster immunization. Our results showed that strong TH1 responses were induced in groups of SLA plus imiquimod as well as SLA plus BCGafter immunization. These responses included smaller footpad thickness, lower parasite load in lymph node, and higher proliferative response of lymph node cells to SLA, higher levels of interferon ;gamma in culture supernatant of lymph node cells, and higher levels of IgG, and IgG2a in sera. The data supports the possibility of using imiquimod as a suitable adjuvant in leishmania vaccination.